Role of Kampo Medicine in Integrative Cancer Therapy. (22nd August 2013) - Yamakawa, Jun-ichi; Motoo, Yoshiharu; Moriya, Junji; Ogawa, Masao; Uenishi, Hiroaki; Akazawa, Sumiyo; Sasagawa, Toshiyuki; Nishio, Matomo; Kobayashi, Junji
Abstract : Clinical trials to date demonstrate that standard cancer treatments are currently the most efficient treatments for large numbers of cancer patients. Cancer treatments will increasingly require approaches that allow patients to live with cancer, by increasing their natural healing power and tumor immunity, as well as attenuating the progression of their cancers, instead of only attacking the cancer cells directly. Complementary and alternative medicine, including Kampo medicine, compensates for the drawbacks of western medicine by increasing patients' self-defense mechanisms. In Japan, clinicians who have studied both western medicine and Kampo treat cancer patients by fusing the two medical systems into a unitary one. The goal of the system is to assist the functional maintenance and recovery of the living body complex with the physical, mental, social, and spiritual balance, rather than addressing direct antitumor effects. In this review, we describe the usefulness of Kampo medicine, especially juzentaihoto, and outline the reports on evidence, in addition to the report on an attitudinal survey about the use of Kampo medicine in cancer treatment in Japan.